Ultrasonographic evaluation of diaphragm fatigue in healthy humans - Camilla R. Illidi; Lee M. Romer (Experimental Physiology)
Abstract Assessment of diaphragm function and fatigue typically relies on the measurement of transdiaphragmatic pressure (Pdi). Although Pdi serves as an index of diaphragm force output, it provides limited information regarding the ability of the muscle to shorten and generate power. We asked whether ultrasonography, combined with Pdi, could be used to quantify changes in diaphragm function attributable to fatigue. Eight healthy men [mean (SD) age, 23 (7) years] completed two tasks on separate occasions: (i) 2 min of maximal isocapnic ventilation (MIV); or (ii) 3 × 5 min of maximal inspiratory resistive loading (IRL). Diaphragm function was evaluated before (PRE) and after each task (POST1, 10–15 min and POST2, 30–35 min) using synchronous recordings of Pdi and subcostal ultrasound traces of the right crural hemidiaphragm during anterolateral magnetic stimulation of the phrenic nerves and progressive CO2 rebreathing. Fatigue was quantified as pre‐ to post‐loading changes in twitch Pdi, excursion velocity (excursion/time) and power (Pdi × velocity). Both tasks resulted in significant reductions in twitch Pdi (P < 0.05). There were no effects of MIV on ultrasound‐derived measures. In contrast, IRL elicited a significant reduction in twitch excursion at POST1 (−16%; P = 0.034) and significant reductions in excursion velocity at POST1 (−32%; P = 0.022) and POST2 (−28%; P = 0.013). These reductions in excursion velocity, alongside the concurrent reductions in twitch Pdi, resulted in significant reductions in diaphragm power at POST1 (−48%; P = 0.009) and POST2 (−42%; P = 0.008). Neither task significantly altered the contractile responses to CO2. In conclusion, subcostal ultrasonography coupled with phrenic nerve stimulation is a promising method for quantifying contractile fatigue of the human diaphragm.